2023
DOI: 10.1021/acs.jchemed.2c00916
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Educational Tool as a Teaching Strategy to Face the Growing Alcohol Consumption in the Student Population

Abstract: Excessive alcohol consumption in adolescence is a worldwide concern because of its numerous negative consequences. It also increases the chance of accidents and may lead to significant impairment of part of the brain, causing learning difficulties. The present work aims to present the development of a forensic educational kit composed of a breathalyzer produced with low cost materials and a colorimetric palette for use in science classes for high school students. The kit’s function is to estimate the ethanol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A paper published in Journal of Chemical Education (JCE) by Carmo, Miranda, and Silva suggested that breath alcohol analysis might be a useful educational tool to teach students about the dangers of overconsumption of alcohol. The authors mentioned that the blood/breath ratio (BBR) of alcohol, with high probability, was somewhere between 1900 and 2400, which is in good agreement with the results from several blood vs breath correlation studies. Labianca’s letter to JCE challenges this conclusion and maintains that variability in the BBR of alcohol is much greater, and this undermines (invalidates) the use of evidential breath-alcohol instruments in forensic science and legal medicine as a way to estimate the coexisting blood-alcohol concentration (BAC) …”
mentioning
confidence: 99%
“…A paper published in Journal of Chemical Education (JCE) by Carmo, Miranda, and Silva suggested that breath alcohol analysis might be a useful educational tool to teach students about the dangers of overconsumption of alcohol. The authors mentioned that the blood/breath ratio (BBR) of alcohol, with high probability, was somewhere between 1900 and 2400, which is in good agreement with the results from several blood vs breath correlation studies. Labianca’s letter to JCE challenges this conclusion and maintains that variability in the BBR of alcohol is much greater, and this undermines (invalidates) the use of evidential breath-alcohol instruments in forensic science and legal medicine as a way to estimate the coexisting blood-alcohol concentration (BAC) …”
mentioning
confidence: 99%
“…In a recent issue of this Journal , Carmo, Miranda, and Silva focus on the timely and pedogogically significant topic of the consumption of alcoholic beverages by school-age adolescents . In this regard, several issues are addressed by the authors.…”
mentioning
confidence: 99%
“…It must be emphasized that Carmo, Miranda, and Silva have produced a fine piece of work. I have only one recommendation: they might consider supplementing their teaching efforts with an added emphasis on the limitations of breath-alcohol analysis addressed here.…”
mentioning
confidence: 99%